2011
DOI: 10.4187/respcare.01239
|View full text |Cite
|
Sign up to set email alerts
|

Organizing Pneumonia and Non-necrotizing Granulomata on Transbronchial Biopsy: Coexistence or Bronchiolitis Obliterans Organizing Pneumonia Secondary toMycobacterium kansasiiDisease

Abstract: Mycobacterium kansasii disease was diagnosed in an 85-year-old woman admitted to the hospital for cough and gradually worsening breathlessness. Transbronchial biopsy indicated either non-necrotizing granulomata or bronchiolitis obliterans organizing pneumonia (BOOP). She was cured with combined therapy of specific anti-mycobacterial medications and systemic steroids. To our knowledge, this is the first report of M. kansasii non-tuberculous mycobacterium disease with a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
(11 reference statements)
1
10
0
Order By: Relevance
“…Recently, cases with certain clinical features have been reported: NTM disease accompanied by histologically-proven organizing pneumonia (OP), also known as bronchiolitis obliterans organizing pneumonia (2,3), in which patients developed acute or subacute symptoms with infiltrates on chest images, and improved dramatically following treatment with a combination of a corticosteroid and antimycobacterial therapy (4)(5)(6). We also found similar cases among our NTM disease patients.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Recently, cases with certain clinical features have been reported: NTM disease accompanied by histologically-proven organizing pneumonia (OP), also known as bronchiolitis obliterans organizing pneumonia (2,3), in which patients developed acute or subacute symptoms with infiltrates on chest images, and improved dramatically following treatment with a combination of a corticosteroid and antimycobacterial therapy (4)(5)(6). We also found similar cases among our NTM disease patients.…”
Section: Introductionsupporting
confidence: 76%
“…Jones et al (5) reported the case of a 58-year-old woman with Mycobacterium avium complex infection, and Starobin et al (6) described an 85-year-old woman with Mycobacterium kansasii infection with biopsy-proven OP, both of which were successfully treated with anti-mycobacterial medication and steroids. In these reports, the authors speculated that OP was induced secondary to NTM disease or that OP was one of the clinicopathologic features of NTM diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary NTM disease is the most common type of involvement and occurs primarily in patients with preexisting structural lung damage such as emphysema or On the other hand, rare cases with different disease entities have been reported: NTM disease accompanied by histologically proven OP in which patients developed acute or subacute symptoms with infiltrates on chest images, and improved rapidly following treatment with a combination of a corticosteroid and anti-mycobacterial therapy (6,(8)(9)(10). Hamada et al (8) reported a 67-year-old woman with fever and dyspnea; her sputum culture confirmed Mycobacterium intracellulare, and transbronchial lung biopsy (TBLB) revealed OP that showed dramatic clinical improvement clinically with corticosteroid and anti-mycobacterial treatment (clarithromycin, rifampicin, and levofloxacin).…”
Section: Discussionmentioning
confidence: 99%
“…Hamada et al (8) reported a 67-year-old woman with fever and dyspnea; her sputum culture confirmed Mycobacterium intracellulare, and transbronchial lung biopsy (TBLB) revealed OP that showed dramatic clinical improvement clinically with corticosteroid and anti-mycobacterial treatment (clarithromycin, rifampicin, and levofloxacin). Jones et al (9) reported a 58-year-old woman with Mycobacterium avium (M. avium) complex infection, and Starobin et al (10) described an 85-year-old woman with Mycobacterium kansasii infection with biopsy-proven OP; both cases were successfully treated with anti-mycobacterial treatment (rifampicin, ethambutol and isoniazid, ethambutol, rifampin, respectively) and corticosteroids. In these reports, the authors considered that OP was probably induced secondary to NTM disease or that OP was one of the clinicopathological features of NTM lung diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 22 cases of M. kansasii pleural effusion were reported between 1980 and 2020 [2][3][4][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. These included 13 men (59.0 %) and nine women (40.9%).…”
Section: Demographicsmentioning
confidence: 99%